Growth of Chikungunya Virus in Baby Hamster Kidney Cell (BHK-21-Clone 13) Suspension Cultures - Davis, Jack L. (1971)
This report describes the methods used to obtain high titers of chikungunya virus with suspension cultures of BHK-21-clone 13 cells. The cells were grown at 37 C to a cell concentration of 10(6) to 2 × 10(6) per ml. After maximum cell growth, the cells were inoculated with chikungunya virus at a multiplicity of 1 to 2 50% suckling mouse intracerebral lethal doses (SMICLD(50)) per cell in the spent Eagle's minimum essential medium for suspension cultures (MEMS), or the cell cultures were centrifuged at 200 × g and resuspended in either fresh MEMS or medium 199 prior to inoculation. The medium used had no effect on virus titer. The inoculated cultures were incubated at 34 C until the cell viability dropped to 30%, which usually occurred 28 to 30 hr postinoculation. After these procedures, chikungunya virus titers of log(10) 10.3 to 11.8 SMICLD(50) per ml were obtained.